Sistem Kendali Lampu Otomatis Berbasis Iot (Internet Of Things) Menggunakan Node Mcu - Hendi Setiawan; Farzin Abdaoe; Kevin Perdana (LPPM Sekolah Tinggi Teknologi Indonesia Tanjungpinang, 2020)
IoT (Internet of Things) is a concept that aims to expand the benefits of continuously internet connectivity. IoT (Internet of Things) can be used in a room as a tool to control electronic equipment that can be operated with a smartphone application via an internet connection. The application of the Internet of Things (IoT) based light control system uses the NodeMCU ESP8266 module as a microcontroller and the Android application as a controller. This system is used to control lights on or off. Also in this system design also uses a relay that is used as a liaison lamp with the system. From the results of testing and analysis, the control of electronic equipment on the lamp control system operates according to the instructions given. As long as the system is connected to the internet network stably and continuously, there will be no obstacles in the IoT (Internet of Things) based light control system using a NodeMCU.